Effects of Newcastle disease virus infection on chicken intestinal intraepithelial natural killer cells - Abdolmaleki, Mostafa; Yeap, Swee Keong; Tan, Sheau Wei; Satharasinghe, Dilan Amila; Bello, Muhammad Bashir; Jahromi, Mohammad Zareian; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini (Frontiers Research Foundation, 2018)
The intestinal intraepithelial natural killer cells (IEL-NK) are among the earliest effectors of antiviral immunity in chicken. Unfortunately, their role during Newcastle disease virus (NDV) infection remains obscure. Previous study has reported the development of a monoclonal antibody (mAb) known as 28-4, which is specifically directed against the CD3− IEL-NK cells. In the present study, we used this mAb to investigate the effects of velogenic and lentogenic NDV infection on avian IEL-NK cells. Our findings revealed that chickens infected with velogenic NDV strains have a reduced population of purified CD3−/28-4+ IEL-NK cells as determined by flow cytometry. Furthermore, the CD3−/28-4+ IEL-NK cells from chicken infected with velogenic NDV strains were shown to have a downregulated expression of activating receptors (CD69 and B-Lec), effector peptide (NK-LYSIN), and IFN gamma. On the contrary, the expression of the inhibitory receptor (B-NK) and bifunctional receptor (CHIR-AB1) were upregulated on these purified CD3−/28-4+ IEL-NK cells following velogenic NDV infection. Meanwhile, the lentogenic NDV demonstrated insignificant effects on both the total population of CD3−/28-4+ IEL-NK cells and the expression of their surface receptors. In addition, using real-time PCR and transmission electron microscopy, we showed that CD3−/28-4+ IEL-NK cells were susceptible to velogenic but not lentogenic NDV infection. These findings put together demonstrate the ability of different strains of NDV to manipulate the activating and inhibitory receptors of CD3−/28-4+ IEL-NK cells following infection. Further studies are, however, required to ascertain the functional importance of these findings during virulent or avirulent NDV infection.